Safety in residential buildings - evacuation from residential buildings without fire escape stairs - Jevtić, Radoje (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: Safety in high residential buildings presents a very important and always actual task. In case of some unforeseen and dangerous occurrences, their residents must be evacuated. Fire, earthquakes, and terrorism are only some of such situations. The speed of evacuation from high residential buildings depends on many different factors. A particularly difficult and complex evacuation task concerns buildings without fire escape stairs. Methods: The modeling method was used in this paper. Based on a real object – a residential building, an appropriate simulation model was realized in appropriate simulation software. Results: The results of this paper have shown that, out of four scenarios, the fastest evacuation was for the evacuation speed of 1.75 m/s. The first two scenarios did not report any jams, unlike the third and fourth scenario; in the third scenario, the occupants’ speeds were 0.75 m/s and 1.25 m/s while in the fourth scenario, the simulated occupants’ speeds were from 0.75 m/s to 1.75 m/s. Conclusion:The usage of appropriate simulation software enables fast, precise, safe and cheаp calculation of evacuation times and it can significantly improve evacuation procedures and evacuation strategies.